NiO/MnO2 nanocomposite in addition of layered Reduced Graphene oxide (RGO) electrode for accountable supercapacitor application - Gayathri Thangavel; Kavitha Balakrishnan; Nirmala Murugesan (Zaštita Materijala)
Reduced Graphene oxide/Nickel oxide/Magnesium dioxide) RGO/NiO/MnO2 nanocomposite electrode was successfully prepared by simple co-precipitation method. The synthesised nanocomposite was characterised by XRD, FESEM, EDAX, FTIR, UV, CV, GCD, EIS. The RGO/NiO/MnO2 nanocomposite was pretreated by ultrasonication, followed by thermal annealing at 350 oC. The crystalline face and size of nanocomposite were analysed by X-Ray Diffraction (XRD). The sandwich-like structure of RGO/NiO/MnO2 was analysed by Scanning Electron Microscope (SEM). This structure promoted an efficient contact between electrolyte and active materials, and the distinct architecture could offer fast transfer channels of ion and electrons. The nanocomposite exhibited high conductivity owing to the presence of RGO. The electrochemical performance of prepared nanocomposite was done by Cyclic Voltammetry (CV), Galvanostatic charge discharge (GCD), Electrical Impedance Spectroscopy (EIS). The synthesised RGO/NiO/MnO2 nanocomposite acquired high specific capacitance of 1167F/g at current density of 1 A/g. The low cost, low temperature RGO/NiO/MnO2 nanocomposite electrode could be the promising electrode for Energy storage devices.